Measuring Pro-Poor Growth with Non-Income Indicators - Stephan Klasen; Kenneth Harttgen; Melanie Grosse (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2005)
One existing shortcoming of current pro-poor growth concepts and measurements is that they are completely focused on income. But growth that is declared to be pro-poor where the measure is based only on income must not automatically imply improvement in the nonincome (or social) dimension of poverty. In our paper, we introduce the multidimensionality of poverty into the pro-poor growth measurement by applying the growth incidence curve to non-income indicators. We investigate if growth in non-income indicators was absolutely and relatively pro-poor. Furthermore, we investigate if the incomepoor benefited from social improvements in linking the development of non-income indicators to the position in the income distribution. We illustrate this empirically for Bolivia between 1989 and 1998 and find that growth was pro-poor both in the income and in the non-income dimension, but results are less clear for the non-income development of the income-poor.
Keywords: D30; O12; I30; O10; 330; Pro-Poor Growth; Multidimensionality of Poverty; Growth Incidence Curve; Bolivia.